Experimental study on fault ride-through capability of VSC-based HVDC transmission system - Ngo Minh Khoa; Nguyen An Toan; Doan Duc Tung (My University, 2021)
Experimental study on fault ride-through capability of VSC-based HVDC transmission system
Keywords: Fault ride-through; VSC-HVDC; Truyền tải điện DC